APIs for business : security, privacy, and new markets (Apress, 2023)
APIs are becoming increasingly important in businesses. APIs help develop the ways things work in business as well as allow the business to grow and explore how they can provide more goods and services to their customers. This course shortly explains how and why a business could achieve this. We will explore what APIs are and how they fit in the world of software development and how they are being applied in old and new technology.